The puppet, the rag doll (Journal of Parents and Teachers, 2025)
: In this article, José Luis Moya Palacios discusses techniques that help children relax through play and imagination, such as rag dolls, puppets, the tree that waited for spring, and the island of "San Jamás," which help teach body awareness, breathing, and cognitive control. The author explains that the sessions are progressive, short and involve family follow-up, which helps to promote autonomy and positive change. Playful, audiovisual and instrumental materials are used for these sessions. These techniques aim to improve children's emotional state and physical well-being
Keywords: Play, Imagination, Emotional, Control, Relaxation and Children.